Complex resistance mechanisms in multidrug-resistant Pseudescherichia vulneris from a Healthy Cat: Unveiling genomic architecture and public health implications - Cabral, Stella; Ballaben, Anelise S. [UNESP]; Ramos, Carolina A.; Ferreira, Joseane Cristina; Chandler, Mick; Varani, Alessandro M. [UNESP]; da Costa Darini, Ana Lúcia (Elsevier, 2025)
Antimicrobial resistance is a critical global public health challenge. Pseudescherichia vulneris is an opportunistic pathogen that carries resistance genes and can invade and colonize various sites in both humans and animals. In this study, we characterized a strain of P. vulneris isolated from the intestinal tract of a healthy cat. Phenotypic analysis revealed that P. vulneris G3 exhibited a multidrug-resistant (MDR) phenotype, remaining susceptible only to cefoxitin, levofloxacin, and ertapenem. Whole-genome sequencing identified a circular chromosome harboring multiple virulence factors commonly found in the Enterobacteriaceae family. Notably, a 300 kb incompatibility group HI2 megaplasmid (pIncHI2A) was detected, carrying a conjugation module and a resistance module with a scrambled structure, reflecting intense activity of mobile elements, such as insertion sequences (e.g., IS26 and ISEcp1), class I integrons, and degenerated transposons (e.g., a Tn402-like element carrying mercury tolerance). The resistance module harbors 15 antibiotic resistance genes (aac(3)-IIa, aac(6’)-Ib10, aph(6)-Id, aph(3”)-Ib, ant(3”)-Ia, bla CTX-M-15, bla TEM-1B, bla OXA-1, sul2, qnrB20, dfrA14, tet(A), tetR, catB3, and catA1), most of which are associated with these mobile elements. Additionally, genes conferring tolerance to tellurium and arsenic, copper/nickel/cobalt efflux pumps, and a type II HipBA toxin-antitoxin system were identified. Given the relevance to the One Health approach, if P. vulneris G3 were to become a zoonotic pathogen, the infections it causes would likely be challenging to treat. This study reports the first identification of a pIncHI2A in P. vulneris, revealing the complex genetic structure underlying MDR, and underscores the need for ongoing surveillance of resistance genes across human, animal, and environmental reservoirs. Impact statement Antimicrobial resistance poses a significant global public health threat. This study highlights the multidrug-resistant (MDR) nature of Pseudescherichia vulneris G3, isolated from a healthy cat's intestinal tract, and its potential implications within the One Health framework. By identifying a unique 300 kb IncHI2 megaplasmid harboring 15 resistance genes and mobile genetic elements, this research emphasizes the pathogen's capacity for genetic plasticity and the risk of zoonotic transmission. The findings underscore the urgent need for comprehensive surveillance of resistance determinants across human, animal, and environmental reservoirs to address the escalating challenge of antimicrobial resistance effectively.